Evolution Sucks (London Journal of Research In Science: Natural and Formal, 2025)
The article deals with evolution and the environment. I assume the unproven claim that all life is generated through evolution. In the chapter titled “Evolution Sucks” I demonstrate that it can have sometimes negative consequences. Although there is no alternative academic explanation, I illustrate some of the ‘disadvantages’ of Darwin’s theory. In the final chapter “The Glut Society” I reference some older books on climate change and the environment in general.